Infrastructure Design and Experiment of SDN-Based NICE - Qian Wang; Huiling Zhao; Xinping Wang; Enhui Liu; Fan Shi (Dianxin kexue)
With the development of new applications and technologies,carriers are facing more challenge on operating network, especially facing new requirement on improving network intelligence. Beginning with technology trend of network intelligence capabilities and software defined networking, the main features of SDN-based network intelligence capability enhancement（S-NICE）were described, as well as the infrastructure designed and deployment solutions. The experimental cases in current network were also discussed.